Role of the High-Affinity Zinc Uptake znuABC System in Salmonella enterica Serovar Typhimurium Virulence - Campoy, Susana (American Society for Microbiology, 2002)
The Salmonella enterica serovar Typhimurium znuABC genes encoding a high-affinity zinc uptake system and its regulatory zur gene have been cloned. Salmonella serovar Typhimurium zur and znuC knockout mutants have been constructed by marker exchange. The 50% lethal dose of the znuC mutant increased when either orally or intraperitoneally inoculated in BALB/c mice, while virulence of the zur mutant decreased only when mice were intraperitoneally challenged.